(untitled) (Medical Forum Monthly, 2024)
Objective: To study the Fate of patients of Hepatitis C on antiviral therapy. Study Design: Prospective Study. Place and Duration of Study: This study was conducted at the Idris Teaching Hospital Sialkot from January 2016- December 2017. Materials and Methods: One Hundred patients of hepatitis C on antiviral therapy were included in this prospective study. All the patients of hepatitis C were diagnosed by kit method and diagnoses was further confirmed by quantitative PCR before start of antiviral therapy. Liver function tests, quantitative PCR, blood picture were also measured before start of antiviral therapy. Abdominal Ultra sound examination was also conducted to see the exact liver picture. Following antiviral therapy was used in all hepatitis C patients included in the study. Sofsububir 400mg (OD), 2. Daclatasvir 60mg (OD), 3. Rivavirin 400mg (TDS) These tests were repeated after completion of the therapy. A performa was designed to record age, gender and above tests. An informed consent was also taken by the patients included in the study. Permission of ethical committee of the institute was also considered before collecting and publishing data. The results were analyzed on SPSS version 10. Results: The frequency of hepatitis C was seen maximum 37 (37%), male 15% and female 22% at age group 31- 40 years and it was minimum 04 (04%), male 01% and female 03% at the age group 61 & above years as shown in table no. 1. At the end of therapy 96 (96%), male 45% and female 51% were cured but 04 (04%) patients of hepatitis C were not cured as shown in table no.03. With regard to complications at the end of antiviral therapy it was observed that anemia was seen in 25 (25%) patients, acities were seen 13 (13%) patients, Hepatic Encephalopathy in 03 (03%) and liver cirrhosis in 02 (02%) patients of hepatitis C as shown in table no. 2. Conclusion: It was concluded on follow up that there were complications (Anemia, Acities, Cirrhosis, Hepatic Encephalopathy etc) in patients of Hepatitis C even treated by antiviral therapy